Systemicity of banana bunchy top viral infection in the Kisangani region of the Democratic Republic of Congo - Djailo, B.D.; Lokana, J.; Ngama, F.; Nkosi, B.I.; Blomme, Guy (Academic Journals, 2016)
In order to evaluate the systemicity of BBTV from one plant of the mat to the physically attached shoots, 60 mats both of “Yangambi Km5”, Musa AAA and those of the false horn plantain “Libanga Likale”, Musa AAB showing severity levels from 0 to 5 were selected in backyards in Kisangani. In addition, 30 sucker corms per genotype were put under macro-propagation and leaf samples of lateral shoots that had emerged were tested using triple antibody sandwich-enzyme linked immuno sorbent assay (TAS-ELISA). In the backyards, for mats with no visible banana bunchy top disease (BBTD) symptoms, none of the analyzed mats with a total of 29 plants of “Yangambi Km5” and of 35 plants of “Libanga Likale” tested ELISA positive, indicating the absence of the BBTV infection. However, for the severity levels of one to five, 32 to 63.5% of plants in the mats were ELISA positive for “Yangambi Km5”, while 34.9 to 73.2% of plants from “Libanga Likale” tested positive for BBTV. After macro-propagation, 100% of lateral shoots of both cultivars at BBTD severity levels 4 and 5 tested positive. On the other hand, none of the lateral shoots at level 0 tested ELISA positive. However, for levels 1 to 3 some ELISA negative plantlets (40 to 23% for “Yangambi Km5” and 53 to 15% for “Libanga Likale”) were observed. This study indicates the need for the complete destruction of all mats harbouring plants with BBTD severity levels of 3, 4 and 5. Macro-propagation of suckers with severity level 1 symptoms could produce virus-free plantlets but ELISA testing of the lateral shoots is essential to pinpoint the virus-free plantlets.